2022
DOI: 10.1016/j.stemcr.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by DREADD reveals the therapeutic effect of human iPSC-derived neuronal activity on functional recovery after spinal cord injury

Abstract: Transplantation of neural stem/progenitor cells (NS/PCs) derived from human induced pluripotent stem cells (hiPSCs) is considered to be a promising therapy for spinal cord injury (SCI) and will soon be translated to the clinical phase. However, how grafted neuronal activity influences functional recovery has not been fully elucidated. Here, we show the locomotor functional changes caused by inhibiting the neuronal activity of grafted cells using a designer receptor exclusively activated by designer drugs (DREA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…Our previous works reported that the grafted cells migrated rostrally and caudally in mice (Ishii et al, 2006; Ito et al, 2021; Kawai et al, 2021; Kitagawa et al, 2022) and marmoset (Iwanami et al, 2005), which increased the connection between grafted cell‐derived neurons and host spared interneurons and fibers around lesion area. Although the tendency of circuit formation between grafted cells and rostral thoracic‐projection or lumbar‐projection supraspinal neurons as well as which way contributes more function recovery needs to be further studied, this work provided a kind of anatomical distribution pattern of supraspinal inputs to rostral and caudal spinal segments, which mapped the relative location of CSNs and RNs projecting to T9‐vertebral (rostral) and T13‐vertebral level (caudal).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous works reported that the grafted cells migrated rostrally and caudally in mice (Ishii et al, 2006; Ito et al, 2021; Kawai et al, 2021; Kitagawa et al, 2022) and marmoset (Iwanami et al, 2005), which increased the connection between grafted cell‐derived neurons and host spared interneurons and fibers around lesion area. Although the tendency of circuit formation between grafted cells and rostral thoracic‐projection or lumbar‐projection supraspinal neurons as well as which way contributes more function recovery needs to be further studied, this work provided a kind of anatomical distribution pattern of supraspinal inputs to rostral and caudal spinal segments, which mapped the relative location of CSNs and RNs projecting to T9‐vertebral (rostral) and T13‐vertebral level (caudal).…”
Section: Discussionmentioning
confidence: 97%
“…Instead, a consecutive hM3Dq stimulation of the CST may achieve simultaneous amelioration of circuit/behavioural activities enhancing synaptic activity 45 , 46 . Furthermore, inactivating CST function by CST-DREADDs would better help provide evidence of the host-to-graft connectivity 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Connection mapping using trans-synaptic rabies viruses, especially the monosynaptic modified rabies viruses, could provide useful insights about the integration and functional connection of graft-derived neurons [ 41 , 42 ]. In addition, deactivation/activation of grafted neurons using chemo-genetic or optogenetic approaches could be very helpful to determine the contribution of grafted neurons in functional recovery [ 43 , 44 ]. It will be very interesting to determine whether different neuronal phenotypes differentiated from grafted NPCs could play varying roles in restoring functional recovery.…”
Section: Discussionmentioning
confidence: 99%